Palmoplantar Psoriasis and Panchakarma: A Comprehensive Treatment Approach (AYUSHDHARA, 2024)
Palmoplantar psoriasis is a chronic type of psoriasis presenting with hyperkeratotic, pustular or mixed forms. This condition can develop in any age, without distinct gender preference. Research indicates that psoriasis affects 2-5% of the population, with 3-4% of those affected having palmoplantar psoriasis. Material and methods: we are presenting a case of 73 years old male presenting with blackish discoloration in bilateral palm and sole associated with itching, burning sensation and cracks since 15 years, treated with Virechana and Basti karma. Results: There was noteworthy improvement in the clinical presentation. Conclusion: Understanding the involvement of Dosha, Dhatu and Samprapti prior to the treatment plan, plays a major role in the Chikitsa. Kushta being a Dhatugata vyadhi, which requires repeated Shodhana and also further Rasayana should be adopted to avoid its recurrence.